Study to evaluate the safety and tolerability of Streptococcus salivarius eK12, a genetically modified strain derived from the oral probiotic S. salivarius K12: Results from a randomized, double-blind, placebo-controlled, parallel-group clinical trial - Di Pierro, Francesco; Bugti, Ali Akbar; Bano, Aasiya; Kara, Mehtap; Ujjan, Ikram; Mumtaz, Nasreen; Gull, Yasmeen; Cazzaniga, Massimiliano; Bertuccioli, Alexander; Tanda, Maria Laura; Zerbinati, Nicola; Hameed, Sumbal; et al. (Frontiers in Nutrition, 2025)
In recent years, genetically engineered probiotics have gained increasing scientific interest owing to their potential applications in human health and nutrition. Streptococcus salivarius K12 is a well-established oral probiotic with an excellent safety record, and a genetically modified derivative, S. salivarius eK12, has been recently developed to enhance its functional properties. The present study evaluated the safety and tolerability of S. salivarius eK12 administered as a dietary supplement in healthy adults. In a randomized, double-blind, placebo-controlled, parallel-group study conducted at the Jam Ghulam Qadir Civil Hospital, Hub, Pakistan (March–August 2025), 29 healthy adults (18–60 years) were assigned to receive S. salivarius eK12 (n = 13) or placebo (n = 16). Participants consumed one orally dissolving tablet twice daily (10 billion CFU/day) for 1 month, followed by 3 months of observation. This dose corresponded to approximately 10 times the level typically used in commercial probiotic formulations. Safety assessments included systemic, oral, and gastrointestinal examinations; self-reported questionnaires; vital signs; body weight; and laboratory investigations encompassing hematology, liver and renal function, electrolytes, HbA1c, thyroid profile, urinalysis, stool occult blood, bacterial culture, and inflammatory markers C-reactive protein (CRP), ferritin, and procalcitonin. All participants completed the study. Streptococcus salivarius eK12 was well-tolerated, with no serious adverse events (AEs) or discontinuations. Clinical, oral, and gastrointestinal examinations were unremarkable, and self-reported symptoms were minimal and comparable to placebo. Laboratory parameters and inflammatory markers remained within normal limits without clinically meaningful deviations. Stool and urine analyses were normal, and bacterial cultures were consistently negative. Extended follow-up revealed no delayed or cumulative adverse effects. These results provide the first clinical evidence that S. salivarius eK12, administered at 10 billion CFU/day for 1 month, is safe and well-tolerated in healthy adults. No adverse clinical or laboratory findings, and no evidence of infections or related complications, were observed during 4 months of monitoring, supporting its safe nutritional use and further clinical development.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT06380270.